2008
DOI: 10.1111/j.1742-1241.2008.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing hypertension in cardiology practice according to risk profile

Abstract: Cardiologists play a central role in managing hypertensive patients, although recent surveys reveal a marked discrepancy between cardiologists' appreciation of their patients' risk status and the measures taken to reduce that risk. The diagnosis and the management of hypertension, in fact, must be viewed today not in isolation, but as part of a patients' global cardiovascular (CV) risk, resulting from the concomitant presence of a variety of risk factors, organ damage (left ventricular hypertrophy, carotid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 91 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…Chung et al (225) demonstrate that vitamin D is inversely associated with lacunes, white matter hyperintensites and deep microbleeding, in profound white matter, not elsewhere, suggesting a high impact on small vessel disease. Moretti et al (226) hypothesize that vitamin D might act on the altered control of CBF [249][250][251][252][253][254] and in the distorted neurovascular coupling system [255][256], both heavily impaired in small vessel dementia. Intracerebral calcium, intimately regulated by vitamin D, interferes with vessel activation.…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Chung et al (225) demonstrate that vitamin D is inversely associated with lacunes, white matter hyperintensites and deep microbleeding, in profound white matter, not elsewhere, suggesting a high impact on small vessel disease. Moretti et al (226) hypothesize that vitamin D might act on the altered control of CBF [249][250][251][252][253][254] and in the distorted neurovascular coupling system [255][256], both heavily impaired in small vessel dementia. Intracerebral calcium, intimately regulated by vitamin D, interferes with vessel activation.…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, recommendations from national (local) and international guidelines should always be taken into account when starting any antihypertensive strategy, because they are based on the results of randomized controlled clinical trials, which have tested the clinical effi cacy, safety and tolerability of different drug classes according to the principles of the modern evidence-based medicine [ 12 , 13 ]. Also, probability to experience a drug-related adverse reaction or an adverse event to prescribed antihypertensive medication, as well as tolerability and safety profi le of each selected drug class or molecule may impact the decision on when, how and how much to treat individual hypertensive patients [ 19 ]. Furthermore, these factors may infl uence persistence and adherence of patients to prescribed antihypertensive drugs [ 20 ] (Chap.…”
Section: How To Choose the Best Strategy To Achieve Blood Pressure Comentioning
confidence: 99%
“…This may help in defi ning different forms of hypertension (e.g. isolated clinic hypertension, 'early morning' hypertension, 'masked' hypertension, 'sustained' hypertension, resistant or pseudo-resistant hypertension) [ 18 ], as well as to better identify the most appropriate therapeutic options among currently available antihypertensive drug classes [ 19 ]. In addition, recommendations from national (local) and international guidelines should always be taken into account when starting any antihypertensive strategy, because they are based on the results of randomized controlled clinical trials, which have tested the clinical effi cacy, safety and tolerability of different drug classes according to the principles of the modern evidence-based medicine [ 12 , 13 ].…”
Section: How To Choose the Best Strategy To Achieve Blood Pressure Comentioning
confidence: 99%
“…Among other factors linked to time constraints during the visit, incomplete awareness of the efficacy of profiling the risk of patients and of timely interventions, inadequate knowledge and application of guidelines and recommendations for cardiovascular risk management may also be reported. [6] A global survey conducted on 825 general practitioners (GPs) from different countries worldwide (n = 75 Italians), recently confirmed an insufficient knowledge and discrepant behaviours, as far as cardiovascular risk management is concerned. [7] A more recent survey on cardiovascular risk perception and management by cardiologists also confirmed that there is room for improvement when treating cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 97%